Debating E-voting throughout Europe: constitutional structures, parties' concepts and Europeans' perceptions - Borucki, Isabelle; Hartleb, Florian (Frontiers in Political Science, 2023)
Techno-optimists with a more cosmopolitan focus agree that E-voting lies at the heart of implementing e-government and digitalization into democratic structures. The example of the “e-state” Estonia proves the relevance: E-voting has been in (legal) practice since 2005, and research can take much empirical evidence from this laboratory for digital innovation. The fact that Estonia is an exception to the rule within the European Union (EU) member states explains the comparative approach to the (possible) legal framework for eparticipation. With focusing on liberal democracies' constitutional predefinitions, voting procedures in the virtual age have not been compared yet. However, we have yet to learn much about the extent to which E-voting exists in European constitutions, even after one generation of intense debate about its possible implementation. Perceptions of E-voting matter because of the omnipresent digital transformation and discussions about how democracies (could) digitalize. E-voting represents a bottom-up part of top-down e-government and, through this, digital transformation. This research explores whether party policies, legal frameworks, and citizens' perceptions resemble E-voting on the national and European levels. To explore this question, several mixed-methods approaches are used. The question of “legalistic opportunity structures” is approached by relying on legal frameworks of European member states, parties' policies derived from their manifestos, and survey data from three Eurobarometer waves. Using a dictionary approach, the research design analyses the constitutions, electoral laws and manifestos of parties running for the European elections, combined with a classic analysis of surveys. Therefore, these sources are analyzed using several mixed methods approaches. The results have broader implications that we need to study in more detail what the digital transformation and the constitutionalization of electronic decision-making entail to develop a digital democracy and link it to a public sphere throughout Europe. Ultimately, it is analyzed whether the EU will push its member states to E-voting and implement E-voting for European elections. This would question the normative basing of democracy and how responsivity is brought into place.